FRACTIONAL ANISOTROPY AND MEAN DIFFUSIVITY VALUE IN 2ND GRADE OF DEGENERATIVE CERVICAL CANAL STENOSIS - Cendikiawan, Hans; Utomo, Sri Andreani (Faculty of Vocational Studies, Universitas Airlangga, 2019)
Background: By using T2 weighted image (T2WI) of Magnetic Resonance Imaging (MRI), a radiologist can classify degenerative cervical canal stenosis (DCCS) into three grade, but there is no correlation between stenosis classification with clinical symptoms. It means that radiologist need a new parameter to make an early detection for spinal cord injury (SCI). Purpose: Proving decrease of FA and increase of MD at the most proximal level of 2nd grade DCCS patient compared with C1-2. Method: Cervical MR examination with 15-direction DTI sequens was performed on twenty one patient with neurological signs and symptoms of 2nd grade DCCS. Apparent FA and MD maps were generated on axial plane. The FA and MD measurements in each individual were made at the most proximal level of 2nd grade DCCS and C1-2. Wilcoxon rank sump test was used to compare FA and paired t-test was used for MD. Result : There are significant differences for FA (p = 0,00) and MD (p = 0,00) at the most proximal level of 2nd grade DCCS compared with C1-2. Conclusion: This research shows that FA and MD value at DTI sequens can be used for SCI early detection at 2nd grade DCCS patient